Symposium 4: Reflections on Hybridity in the Malta Networked Learning Forum 2021 - Lister, Pen; Cutajar, Maria; Calleja, James (Proceedings of the International Conference on Networked Learning, 2024)
This paper discusses the practicality, successes and possible failures of the Malta Networked Learning (NL) Forum held in May 2021. The forum was held in a hybrid synchronous face-to-face and virtual context, with a wide range of international participants, planned at short notice due to continuing uncertainty of Covid-19 restrictions. The paper outlines contexts and understandings of hybridity in both events and pedagogical approaches, noting varying definitions and concepts that may utilise this term to indicate forms of barrier breaking, overcoming limitation or supporting flexibility. Further context highlights recent literature concerning other digitally hybrid conference events, the need for which have been accelerated in light of the Covid-19 pandemic and additional considerations of climate change for reducing the carbon footprint of academic communities. Discussion leads to the type of hybridity implemented for the Malta NL Forum in May 2021, where pandemic international travel restrictions, local regulations and participant planning uncertainty required the adoption of a face-to-face and virtual synchronous event. The local organising team (authoring this paper) provides commentary to critically reflect on the strengths and weaknesses of the modality adopted. Emphasis is placed on designing for hybridity in future events, to improve planning and organisation for flexible and agile awareness to support the full range of participants in hybrid contexts and activities. The paper attempts to support those whose role is to convene and host similar events aiming to foster rewarding engagement for those participating, both presenting as well as attending.